Efficient Synthesis of Heterocyclic Neurotensin Receptor Ligands by Microwave-Assisted Aminocarbonylation - Lang, Christopher; Gmeiner, Peter (Synthesis, 2013)
Marking the heterocyclic neurotensin receptor antagonist SR142948A as a lead compound, the development of an efficient and a practical synthetic route to heterocyclic aryl carboxamides is reported. Thus, a highly efficient and flexible access to these carboxamides was elaborated by taking advantage of microwave-assisted aminocarbonylation reaction mediated by Mo(CO)6, Herrmann’s palladacycle, [(t-Bu)3PH]BF4, and DBU.
Keywords: aminocarbonylation; microwave; aryl bromide; palladium catalysis; palladacycles; medicinal chemistry